KECENDERUNGAN KONSUMEN DALAM MEMILIH JENIS IKAN DI RESTORAN DWI MADIUN KELURAHAN GUNUNG SAMARINDA KOTA BALIKPAPAN PROVINSI KALIMANTAN TIMUR - Nurul Makiyah R; Fitriyana; Zul Asman Randika (2339-1324, 2017)
This research is carried out to determine consumers fish favourite in Dwi Madiun restaurant and to investigate relationsip between price and consumers income to fish choice in Dwi Madiun restaurant. Simple random test is used in this experiment, which individuals is chosen randomly and entirely by chance if see fit as data source. All data was analysed by chi-squared distribution analysis. Result shows consumers tendency to choose favourite fish (milkfish, pomfret, white snappers, red snappers, and chicken), consumers tend to choose the same fish for their meal. There are no significant relationship between price and consumers income to costumers fish choice in Warung Dwi restaurant.